Genotype prediction in the fragile X syndrome. Issue 12 (December 1991) - Hirst, M C; Nakahori, Y; Knight, S J; Schwartz, C; Thibodeau, S N; Roche, A; Flint, T J; Connor, J M; Fryns, J P; Davies, K E
Abstract : Fragile X positive, mentally retarded males have been shown to have an insertion or amplification of DNA sequences at, or close to, the site of expression of the fragile site. We show here the application of the detection of such changes to the diagnosis of affected males and female carriers and the identification of normal transmitting males. One fragile X negative male with the clinical features of the Martin-Bell syndrome also possesses an inserted/amplified DNA sequence. The implications of these results for screening for the fragile X syndrome are discussed.